Only his [compact disc, unabridged] - Mallery, Susan (Mallery, Susan. Fool's gold, 2011)
Wedding bells are ringing in Fool's Gold, but not for Nevada Hendrix. Her triplet sisters are engaged, and even her mother has a more active love life than she does. Determined to make a fresh start, she applies for her dream job, only to discover that her new boss is her first love. Tucker Janack agrees to Nevada's 'business only' ground rules. But when great business partners turn out to be so much more, every rule gets broken.